Comments on "Evaluation of entropy generation with thermal radiation on MHD Carreau fluid stream past a wedge". (2021) - Awad, M.M.
Abstract: The magnetic parameter (M) is dimensional. In addition, the first associated boundary condition at y = 0 is incorrect.